A corporal(idade) discursiva à sombra da hierarquia e do poder: uma relação entre Oyěwùmí e Foucault - Rocha, Aline Matos da (2018)
The relation between coporality, hierarchy and power require a very certain understanding. Considering an approximation between the theoretical framework by Michel Foucault and Oyèrónkẹ́ Oyěwùmí, this work intends to approach those concepts to their political, social and discursive reverberances. Oyěwùmí presents the way how gender was incorporated into Ọ̀ yó-̣ Yorùbá precolonial society, due to fact that such society did not assume prior to colonization body and gender as crucial categories and sources of organization and social hierarchy. Prior to the infusion of western categories, the hierarchies among the yorùbá people were expressed by seniority, always relational and mutable. Thus, the main question hereby presented is: how does body organize the relations and the social hierarchies? A reflection on this issue will be adressed through speeches by the metioned authors, mainly how gender, race and class – signs in the body – are hierarchical categories created and crossed by power in order to standardize social relations, circumscribe places and settle life and death.